(3efGgL cJGHI GdCNHGQ hJMQjQgG s - (3Ydj YHO GdaJGM(B, (3cfYGfs ((3YeGf (B:s (3OGQ GdCjGe ddfTQ h GdJhRjY(B,s, 2015)
(3cJGHI eJbOeI ddCNHGQ GdEYdGejI h GdJbGQjQ GdUMajI h GdJWQb Gdi JMQjQ GdNHQ GdUMaj h cP GdGQJbGA HGdYQHjI aj hSGFd GdGYdGe h CNjQG GdJMQjQ h UjGZI GdNHQ(B.s
(3eQGLY U(B.213s
Keywords: (3GdUMGaI(B-(3JMQjQs